Global group work - Cohen, Carol S.; Doel, Mark; Wilson, Mary; Quirke, Deirdre; Ring, Karen A.; Abbas, Sharima Ruwaida (Groupwork, 2012)
This article focuses on the Global Group Work Project’s action research study to explore and identify essential cross-national and cross-cultural elements of social groupwork practice, and to provide a model for international research and collaboration. It details study methods, process and outcome findings, analysis and recommendations. The key finding of the global themes of being together and doing together in social work groups, as well as the identification of local, indigenous practices contribute empirical knowledge about groupwork’s international nature, with implications for teaching, research and practice.